An Omics Perspective on Candida Infections: Toward Next-Generation Diagnosis and Therapy - Smeekens, S. P.; van de Veerdonk, F. L.; Netea, M. G. (Frontiers in Microbiology, 2016)
Candida species can cause severe infections associated with high morbidity and mortality. Therefore, it is essential to gain more insight into the anti-fungal host defense response. The advent of omics technology and development of advanced systems biology tools has permitted to approach this in an unbiased and quantitative manner. This review summarizes the insights gained on anti-Candida immunity from genetic-, transcriptome-, proteome-, metabolome-, microbiome-, mycobiome- and computational systems biology studies and discusses practical aspects and future perspectives.